2021
DOI: 10.1177/21582440211021403
|View full text |Cite
|
Sign up to set email alerts
|

Programming Language Training With the Flipped Classroom Model

Abstract: The flipped classroom method, which could be considered as one of the crucial new generation teaching approaches, is a permutation of the educational activities that are carried out inside and outside of the classroom environment. The main purpose of the present study is to determine the impact of the flipped classroom approach on students’ academic achievement and their attitudes toward programming and methodology at the higher education level. The current study employed a mixed research method as findings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Future research could also attach importance to other factors that may influence video-assisted distance learning, for example, teacher presence (Yu, 2021a), gender, educational level, and personality (Yu, 2021b), as well as challenges that may confront the flipped approach such as technological costs, video suspense, absence, and poor interactions (Taşpolat et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Future research could also attach importance to other factors that may influence video-assisted distance learning, for example, teacher presence (Yu, 2021a), gender, educational level, and personality (Yu, 2021b), as well as challenges that may confront the flipped approach such as technological costs, video suspense, absence, and poor interactions (Taşpolat et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The flipped model has been shown to improve student satisfaction and performance, although it, too, presents challenges when students fail to prepare before class or need assistance in viewing learning content (Akçayır & Akçayır, 2018). In studies of flipped learning in computer programming classes, student performance in the flipped learning environment increased compared both to control groups and previous iterations of a class taught in a traditional format (Ruiz de Miras et al, 2022;Taşpolat et al, 2021). While student feedback is generally positive about this style of learning in programming classes, it has also been suggested that the self-study component can be less effective for more advanced programming topics, necessitating a blend of the traditional and the flipped classroom (Davenport, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the flipped classroom model also uses online learning resources, it is believed that combining online learning with a flipped classroom can open up a new model of blended learning for the relevant courses and increase the effectiveness of online learning (Huang, 2019). Such advantages of flipped classroom as individualized learning, the ability to catch up with those who are absent, increased personal responsibility for their education, increased motivation, development of creative abilities, the ability to save and archive material, and changing the teacher's role to a friendlier one, increasing the time of contact between the teacher and the student, and the opportunity to learn anywhere at any time turn this model into a pedagogical breakthrough (Campillo-Ferrer & Miralles-Martínez, 2021;Taşpolat et al, 2021). In addition, there are some disadvantages: lectures can be uninteresting, students ignore video materials, a passive approach, insufficient technological resources, the inability to teach practical things online, insufficient time to produce materials, etc.…”
Section: Literature Reviewmentioning
confidence: 99%